1998
DOI: 10.1086/302139
|View full text |Cite
|
Sign up to set email alerts
|

Genome Screens Using Linkage Disequilibrium Tests: Optimal Marker Characteristics and Feasibility

Abstract: Linkage disequilibrium (LD) testing has become a popular and effective method of fine-scale disease-gene localization. It has been proposed that LD testing could also be used for genome screening, particularly as dense maps of diallelic markers become available and automation allows inexpensive genotyping of diallelic markers. We compare diallelic markers and multiallelic markers in terms of sample sizes required for detection of LD, by use of a single marker locus in a case-control study, for rare monophyleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 24 publications
1
78
0
2
Order By: Relevance
“…For a single susceptibility allele, Akey et al [2001] reported that with equally frequent haplotypes made up of 2 or 4 biallelic sites, a chi-square test has greater power when based on haplotype than when based on individual SNPs. Their model involves recombination dynamics, but their conclusion is essentially the same as that of Chapman and Wijsman [1998], who showed that with equally frequent alleles, the power of the chi-square test is greater for a multiple allele marker than for a biallelic marker. The results of this investigation suggest that these conclusions can be extended to multiple susceptibility alleles at a disease locus.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…For a single susceptibility allele, Akey et al [2001] reported that with equally frequent haplotypes made up of 2 or 4 biallelic sites, a chi-square test has greater power when based on haplotype than when based on individual SNPs. Their model involves recombination dynamics, but their conclusion is essentially the same as that of Chapman and Wijsman [1998], who showed that with equally frequent alleles, the power of the chi-square test is greater for a multiple allele marker than for a biallelic marker. The results of this investigation suggest that these conclusions can be extended to multiple susceptibility alleles at a disease locus.…”
Section: Discussionmentioning
confidence: 75%
“…; t at the disease locus. The case for a single susceptibility allele is given by Akey et al [2001] and Chapman and Wijsman [1998].…”
Section: Specification Of Alternative Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many LD methods have been well developed currently for complex disease genes, haplotype-based analysis is one of the major statistical methods because haplotypes of multiple single-nucleotide polymorphisms (SNPs) are considered a more informative format of polymorphisms for genetic analysis than single SNP. 1 The classical haplotype-based statistic is to compare haplotype frequencies between affected and unaffected individuals 1,2 or to compare haplotype similarities between affected and unaffected individuals. 3,4 Recently, Zhao et al 5 proposed an entropy-based statistic T PE for a genome-wide association study through a nonlinear transformation of haplotype frequencies.…”
Section: Introductionmentioning
confidence: 99%